Apresiasi Sastra Produktif Penerapan Pendekatan Parafrastis dan Analitis Terhadap Sastra Anak - Riska Nur Magfira Rusdi; Rahma Ashari Hamzah; Ahmad Dzaky Syahrir (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This paper examines the application of paraphrastic and analytical approaches in the appreciation of productive literature, especially for children's literature. Productive literary appreciation is important in fostering children's reading interest and creativity. The paraphrastic approach helps children re-express literary works in their own language, improving understanding and critical thinking skills. On the other hand, the analytical approach allows children to identify intrinsic and extrinsic elements in literary works, providing deeper insights. Through these two approaches, children are not only passive connoisseurs, but also active in creating and exploring new literary works. This paper explains the definition, characteristics, benefits, and examples of the application of both approaches in literary activities in elementary schools. It is hoped that by implementing this method, children can develop a better appreciation of literature and the moral values ​​contained therein, creating a productive and creative learning environment.